GPS MONITORING - Bigoraj, Marcin; Kaźmierak, Kamil; Krupa, Mateusz; Narejko, Ewelina; Pytka, Rafał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The article describes construction and performance of mobile application monitoring position of the mobile device using the built-in GPS. Describes the presentation of the collected data using dedicated web application and demonstrates its capabilities.